2006
DOI: 10.1111/j.1551-2916.2006.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slag Impregnation on Thermal Degradations in Refractories

Abstract: Degradation in bauxite refractory linings used in steel plants is localized in the slag‐impregnated zone of refractories. It is proposed to estimate the contribution of the pressure of the impregnated liquid on the degradation of refractories. The study of the gradient of chemical composition allows for the evaluation of the liquid content, the oxide content in the liquid phase, and the “slag” viscosity. The thermomechanical analysis of a porous refractory impregnated by slag enables us to propose analytical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Practical testing of a wide variety of materials under the same testing protocol showed that the microstructure, chemistry, and intrinsic properties of each individual refractory had, as expected, a significant effect on the thermal shock resistance . Further complicating the mechanical failure of ceramics and refractories in service was the interaction of the refractory with the environment, which was found to significantly change the refractory degradation processes . The infiltration of a liquid phase into the open pores of a refractory material, commonly seen during the use of refractories in metallurgy, had a large negative effect on the thermal cycle resistance …”
Section: Common Failure Modes Of Precast Monolithicsmentioning
confidence: 65%
“…Practical testing of a wide variety of materials under the same testing protocol showed that the microstructure, chemistry, and intrinsic properties of each individual refractory had, as expected, a significant effect on the thermal shock resistance . Further complicating the mechanical failure of ceramics and refractories in service was the interaction of the refractory with the environment, which was found to significantly change the refractory degradation processes . The infiltration of a liquid phase into the open pores of a refractory material, commonly seen during the use of refractories in metallurgy, had a large negative effect on the thermal cycle resistance …”
Section: Common Failure Modes Of Precast Monolithicsmentioning
confidence: 65%
“…Once the REV has been defined it is essential to well identify the state variables to describe the behaviour of the system. As it is not so obvious to do it when dealing with multi-physical problems, the use of a coupling scheme is recommended [9]. This approach simplifies drawing of the physics in presence and their interactions and permits to not forget a coupling effect.…”
Section: Essential Basic Concept Of Thermodynamics and Macroscopic Momentioning
confidence: 99%
“…Factors that control the penetration of molten slag into the refractory include the operating atmosphere, refractory temperature, refractory porosity, pore size distribution, slag composition, and interfacial surface properties of the slag with respect to microstructure and chemistry of the refrac-tory material. 4 To complement the authors' prior work on the effects of temperature gradients on slag penetration, 5 this analysis examines the role of time and oxygen partial pressure in the interactions between synthetic coal slag and Al 2 O 3 refractory materials. While refractories with high Cr 2 O 3 content are considered to be the material of choice in industrial gasifiers, 6 this study focuses on a 99 at.% Al 2 O 3 refractory so as to simplify the degradation analysis to a single chemical system.…”
Section: Introductionmentioning
confidence: 99%
“…10(a)'s Micrograph of a Porous Area near the Top Interface of 5 h Infiltration in Air Atmosphere. Regions Belonging to (3) Contain Higher Concentrations of Fe 2 O 3 Than the Unaffected Al 2 O 3Regions Belong to(4)…”
mentioning
confidence: 99%